ANALYSIS OF FREE ROUTE AIRSPACE AND PERFORMANCE BASED NAVIGATION IMPLEMENTATION IN THE EUROPEAN AIR NAVIGATION SYSTEM - Pavlova, Svetlana; Zadorozhnia, Alina (Proceedings of National Aviation University, 2014)
European Air Traffic Management system requires continuous improvements as air traffic is increasingday by day. For this purpose it was developed by international organizations Free Route Airspace and PerformanceBased Navigation concepts that allow to offer a required level of safety, capacity, environmental performance alongwith cost-effectiveness. The aim of the article is to provide detailed analysis of Free Route Airspace and PerformanceBased Navigation implementation status within European region including Ukrainian air navigation system.